AGROFINANCIALIZATION AND NEW FRONTIERS OF THE SUGAR-ENERGY SECTOR IN BRAZIL: THE CASE OF THE BUNGE GROUP IN THE STATE OF MINAS GERAIS - Féo Castro de Araújo, Daniel; Luiz Araújo Sobrinho, Fernando (PEGADA - A Revista da Geografia do Trabalho, 2023)
The agrofinancialization of agriculture has been a significant driving force for the productive reconfiguration of the territory, mainly based on the logic of commodity production. In the Triângulo Mineiro/Alto Paranaíba region, the internationalization of the sugarcane sector has been marked by the presence of foreign groups, such as the Bunge Sugar and Bioenergy Group, which has a stake in three plants in the region. This article aims to analyze the agrofinancialization of the sugarcane sector in the Triângulo Mineiro/Alto Paranaíba, starting from the territorialization of the Bunge Sugar and Bioenergy Group. The methodology adopted in this research includes a literature review that uses documents and reports made available by international organizations, governments, NGOs, and rural social movements, as well as bibliography found in specialized academic books and journals. This literature review is fundamental for the understanding and construction of the narrative about the subject. The research concludes that Bunge has predominantly appropriated the territory through leasing for sugarcane production, incorporating areas that were previously intended for grain, food, and livestock cultivation. It is important to emphasize that this practice is a consequence of the logic of agrofinancialization of agriculture, which has driven the productive reconfiguration of the territory based on commodity production. Therefore, it is essential to consider social and regional aspects in the planning and regulation of agro-export activities.